Amstirdam coffee ameliorates Lp-PLA2 and the inflammatory response in an atherosclerosis rats - Wirdatun Nafisah; Annia Zhafarina Dalilati; Yuyun Ika Christina; Mochammad Fitri Atho'illah; Muhaimin Rifa'ia; Tengku Natasha Eleena Tengku Ahmad Noor; Alexander Patera Nugraha (Pensoft Publishers, 2024)
Coffee is a kind of daily beverage, and its correlation with cardiovascular disease and atherosclerosis is still debatable. The aim of this study is to investigate the effects of Amstirdam coffee extract (ACE) on lipoprotein-associated phospholipase A2 (Lp-PLA2) and the inflammatory response in atherosclerosis mouse models. The study used 25 Swiss male mice for five groups (n = 5): healthy mice fed a normal diet (N); mice fed a high-fat, high-fructose diet (HFFD); mice fed HFFD and treated with ACE at doses of 104 (D1), 520 (D2), and 5200 mg/kg BW (D3). The levels of Lp-PLA2, regulatory T cells (Tregs) (CD4+CD25+CD62L+, CD4+CD25+IL-10+, CD4+CD25+TGF-+), IL-10 (CD4+IL-10+), and TGF-B (CD4+TGF+) were analyzed using a flow cytometer. Histological analysis of the mouse aorta was done by hematoxylin and eosin (HE) staining. This study indicated a significant increase in total cholesterol (TC), triglyceride (TG), LDL, and Lp-PLA2 levels in the HFFD group. HFFD also reduced HDL, IL-10, and TGF produced by CD4 and Tregs compared with the normal group. ACE at all doses significantly reduced Lp-PLA2 levels compared with the HFFD group (p < 0.05). Interestingly, the administration of 520 mg/kg BW ACE (D2) increased the production of IL-10 significantly compared to other doses (p < 0.05). The D3 group possessed a high TGF- production and Treg expression level significantly different between groups (p < 0.05). Foam cells were mostly found in the aorta of the HFFD group compared to the normal and ACE treatment groups. This study suggested that ACE could reduce Lp-PLA2 enzyme activity and foam cell formation through the immunosuppressive activity of IL-10 and TGF cytokines.